Marginal resection and adjuvant strontium plesiotherapy in the management of feline eyelid malignant peripheral nerve sheath tumours: two cases - Davide Berlato; Ana Rita Serras; Marian Matas Riera; Roberta Rasotto (Journal of Feline Medicine and Surgery Open Reports, 2016)
Case series summary Two cats with a marginally resected eyelid malignant peripheral nerve sheath tumour were treated with adjuvant strontium plesiotherapy a few weeks after surgery. The dose applied in both cases was 200 Gy to the surface, in five fractions, on a Monday–Wednesday–Friday basis. The treatment aimed to achieve a clinical margin of approximately 1 cm around the surgical scar and multiple application fields were required to cover such an area. Local recurrence was not seen in either case after 1330 and 645 days, respectively. Relevance and novel information The majority of periocular malignant peripheral nerve sheath tumours reported in the literature recur after surgery. In the two cases described in this report the combination of surgery and adjuvant plesiotherapy has been able to provide good local control with minimal toxicity. This multimodal approach could be considered as an alternative to aggressive surgery such as enucleation or exenteration.